Travels in Persia - 1627-1629: (Extract from the text by Sir Thomas Herbert, English Traveller, historian) - Jighauri, Nino; Khintibidze, Elguja; თომას ჰერბერტი, Thomas Herbert (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2019)
Thomas Herbert